Analisis Penegakan Hukum Terhadap Tindak Pidana Pelaku Usaha Perikanan Tanpa Izin dan Penggunaan Alat Tangkap Yang Merusak Ekosistem Perikanan (Studi Kasus Putusan Mahkamah Agung Nomor 2868 K/Pid.Sus/2025) - Yogi Darmawan Effendi; Misbahul Huda (Neolectura, 2026)
The fisheries sector plays a vital role in supporting economic growth, food security, and the sustainability of Indonesia’s marine resources. However, violations persist in the form of unlicensed fisheries business activities and the use of fishing gear that damages marine ecosystems, threatening environmental balance within the Fisheries Management Areas of the Republic of Indonesia (WPPNRI). This study examines the regulation of fisheries-related criminal offenses under Indonesian positive law and analyzes judicial considerations in Supreme Court Decision Number 2868 K/Pid.Sus/2025. Using a normative juridical method with statutory, case, and conceptual approaches, this research relies on primary legal materials in the form of relevant legislation. The findings indicate that fisheries business activities must comply with the principles of legality and sustainability, requiring valid licenses such as SIUP, SIPI, and SIKPI. The Supreme Court confirmed that the defendant was legally and convincingly proven to have committed a fisheries-related criminal offense and imposed sanctions in accordance with applicable law. This decision demonstrates the enforcement of legal certainty and the protection of sustainable fisheries resources in Indonesia